Pengembangan Karakter Melalui Dongeng SD Negeri 2 Punggelan - Maulidia, Awalina Farhatul; Nurharini, Atip; Anastasya, Puspa Ayu; Nurfadila, Ratih; Nafiah, Lailatun; Wildan, Risya Faiza Rizqi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Character education is very important for the academic and moral of students, especially elementary school students. In this era, there are still many characters that need to be formed because of the low moral values of students. Educational institutions must synergize to improve the character of elementary school students. One way is to use fairy tale media. Fairy tales are a fun learning approach for students. Fairy tales are stories that contain moral and social values that are useful for shaping the character of elementary school students. Character cultivation can be instilled in students by learning the traits that play a role in the fairy tale. Student character building strategies are carried out by giving examples, habituating reading and listening to fairy tales. This study used qualitative research methods. The purpose of this study is to instill the character of elementary school students through a fairy tale learning approach.